Squad goals - Kendrick, Erika J. (Little, Brown and Company, 2021)
Twelve-year-old Magic Pointdexter comes from a long line of cheerleaders, but to follow in their footsteps, Magic must survive summer camp Planet Pom Poms, audition for a spot on the HoneyBee cheer squad, and steer clear of swoon-worthy Dallas Chase.